2013
DOI: 10.1103/physreve.87.043107
|View full text |Cite
|
Sign up to set email alerts
|

Dust-ion-acoustic supersolitons in dusty plasmas with nonthermal electrons

Abstract: Supersolitons are a recent addition to the literature on large-amplitude solitary waves in multispecies plasmas. They are distinguished from the usual solitons by their associated electric field profiles which are inherently distinct from traditional bipolar structures. In this paper, dust-ion-acoustic modes in a dusty plasma with stationary negative dust, cold fluid protons, and nonthermal electrons are investigated through a Sagdeev pseudopotential approach to see where supersolitons fit between ranges of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
54
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 38 publications
(93 reference statements)
4
54
1
Order By: Relevance
“…Some studies have already confirmed that the weakly nonlinear theory is not an appropriate choice to describe these structures in the auroral regions. In fact, reductive perturbation approach cannot be employed to describe supersolitary profiles . Berthomier et al used Sagdeev pseudopotential to study ion‐acoustic solitary waves and double layers in an unmagnetized three‐component plasma with two‐temperature Maxwellian electrons and fluid ions and verified their results with Viking satellite observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have already confirmed that the weakly nonlinear theory is not an appropriate choice to describe these structures in the auroral regions. In fact, reductive perturbation approach cannot be employed to describe supersolitary profiles . Berthomier et al used Sagdeev pseudopotential to study ion‐acoustic solitary waves and double layers in an unmagnetized three‐component plasma with two‐temperature Maxwellian electrons and fluid ions and verified their results with Viking satellite observations.…”
Section: Introductionmentioning
confidence: 99%
“…Supersolitons are recently [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] discovered nonlinear structures that differ from regular solitons and are characterized by wiggles or subsidiary maxima on the sides of the bipolar electric fields of the solitons. The Sagdeev pseudopotential of the plasma model should have three consecutive local extrema to access the nonzero root from the undisturbed conditions to form supersolitons and thus the pseudopotential profile of supersolitons exhibits a two-subwell-like structure.…”
Section: Introductionmentioning
confidence: 99%
“…Following the seminal work of R.Z. Sagdeev in the 1960s [4], these have been effective modelled by an integrable (pseudo-Hamiltonian) model [5], which was later generalized to take into account different plasma configurations or/and other generic types of electrostatic structures [6]. ESWs in ultrahigh density plasmas permeated by a negative-ion beam will be the focus of this study.…”
Section: Introductionmentioning
confidence: 99%
“…They have delineated the existence regimes of the supersolitons by determining the limiting factors. Ion-acoustic solitons have been studied in three-component unmagnetized plasmas comprising of cold fluid ions and two (cold and hot) electrons having kappadistributions [23]. It was shown that the existence regime of the supersolitons vary significantly with the spectral index kappa.…”
Section: Introductionmentioning
confidence: 99%